Assessment of urinary 15‐F2‐isoprostanes in dogs with urothelial carcinoma of the urinary bladder and other lower urinary tract diseases. (16th September 2020) - Woolcock, Andrew D.; Cheney, Adrienne; Deshuillers, Pierre; Knapp, Deborah; Moore, George E.
Abstract: Background: The 15‐F2 ‐isoprostanes are by‐products of oxidative stress and are increased in the urine of people with lower urinary tract diseases (LUTD), especially urinary neoplasia. Urothelial carcinoma (UC) is the most common urinary neoplasm in dogs. Earlier detection of UC by noninvasive means could lead to improved outcomes. Urinary 15‐F2 ‐isoprostanes potentially could provide this means, but have not been evaluated in dogs with UC. Objective: The objective of this study was to measure urinary 15‐F2 ‐isoprostanes in dogs with UC and dogs with other LUTD. Animals: One hundred seventeen dogs: 46 dogs with UC, 30 dogs with LUTD, and 25 control dogs. Methods: Any dog that was presented with dysuria was eligible for inclusion. Diagnosis of UC was confirmed histologically. Urinalysis was performed in each case, and 15‐F2 ‐isoprostanes quantified by gas chromatography‐negative ion chemical ionization‐mass spectrometry (GC‐NICI‐MS) and normalized to urinary creatinine concentration. Results: Dogs with urinary diseases (UC + LUTD) had higher median urinary 15‐F2 ‐isoprostanes when compared to control dogs (5.92 ng/mg [range, 0.46‐31.03] vs 3.73 [range, 1.8‐7.98]; P = .02). Urinary 15‐F2 ‐isoprostanes were similar in dogs with UC (5.33 ng/mg [range, 0.46‐31.03]) compared to dogs with LUTD (6.29 ng/mg [range, 0.54‐18.93]; P = .47) and control dogs ( P = .06). Dogs with UC had higher qualitative measures of proteinuria ( P = .004), hematuria ( P = .01), and epithelial cells on urinalysis ( P = .002) compared to the other groups. Conclusions and Clinical Importance: Urinary F2 ‐isoprostanes are not useful for the detection of UC in dogs. Future research could evaluate urinary 15‐F2 ‐isoprostanes as a marker of inflammation in disease progression and prognosis.